2019
DOI: 10.1177/0021934719833330
|View full text |Cite
|
Sign up to set email alerts
|

“A Dream Deferred”: How Discrimination Impacts the American Dream Achievement for African Americans

Abstract: The American Dream (TAD) is an ideological symbol of achievement and success in American culture. Historical barriers to equal opportunities and economic attainment through racial discrimination have limited access to TAD for African Americans. Barriers of discrimination also reduce the perception of one’s life satisfaction, which can further affect the beliefs of ever obtaining TAD. The present research evaluated the effects of discrimination and life satisfaction on perceptions of achieving TAD among a sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Firdous et al [69] further examined the relationship between academic achievement and overall life satisfaction among medical students in Pakistan (n = 200) and found a significant positive relationship between academic achievement and overall life satisfaction. In another empirical study investing life satisfaction in African American adults (n = 1081), Armstrong et al [70] found that those who reported having achieved "The American Dream" reported having higher life satisfaction than those who reported not having achieved "The American Dream". In other words, achieving their vision of "The American Dream" was strongly associated with their overall satisfaction with life.…”
Section: Muay Thai and Psychological Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Firdous et al [69] further examined the relationship between academic achievement and overall life satisfaction among medical students in Pakistan (n = 200) and found a significant positive relationship between academic achievement and overall life satisfaction. In another empirical study investing life satisfaction in African American adults (n = 1081), Armstrong et al [70] found that those who reported having achieved "The American Dream" reported having higher life satisfaction than those who reported not having achieved "The American Dream". In other words, achieving their vision of "The American Dream" was strongly associated with their overall satisfaction with life.…”
Section: Muay Thai and Psychological Well-beingmentioning
confidence: 99%
“…We have now reviewed the literature on psychological well-being and found ample empirical evidence confirming that positive emotions [33][34][35][36][37][38][39], engagement [36,[44][45][46][47][48], relationships [51][52][53][54][55][56], meaning [36,[60][61][62][63][64][65], and accomplishment [67][68][69][70][71][72] are important elements that contribute to overall psychological well-being [16]. We have also reviewed recent research on Muay Thai training and found a growing body of empirical work suggesting that Muay Thai training can contribute to positive emotions [40][41][42][43], engagement [49,50], relationships [41,50,[57][58][59], meaning [42,49,…”
Section: Perspectives From An Everlast Master Instructormentioning
confidence: 99%